A Comparative Study on the Type and Severity of Clinical Symptoms of Acute Coronary Syndromes in Men and Women - Mehdi Raei; Azam Hamidzadeh; Akram Sadat Montazeri; Zahra Naeimabadi; Amir Almasi Hashiani (مجله دانشکده پزشکی اصفهان, 2013)
Background: Knowing the symptoms of heart failure and the way they are different among men and women can reduce decision making time in providing diagnostic and therapeutic measures. It can also improve the quality of the response. This study aimed to compare the type and severity of symptoms experienced by men and women with acute coronary syndromes.